2016
DOI: 10.1245/s10434-015-5053-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Outcomes Between Emergency Surgery and Bridge to Surgery for Malignant Obstruction in Right-Sided Colon Cancer: A Multicenter Retrospective Study

Abstract: On the basis of the above results, the postoperative course of the ES group was similar to that of the BS group. In addition, the long-term oncologic outcome of the BS group was similar or slightly better than that of the ES group. BS after colonic stent may be an alternative option for MORC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 19 publications
5
41
1
Order By: Relevance
“…In addition, significantly more lymph nodes were harvested in the stent group. Contrary to our study, however, they did not find a significant difference in 30-day mortality and morbidity 22. A possible explanation for this discrepancy could be that they included considerable fewer patients than the current study and might have lacked power to demonstrate a significant difference.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, significantly more lymph nodes were harvested in the stent group. Contrary to our study, however, they did not find a significant difference in 30-day mortality and morbidity 22. A possible explanation for this discrepancy could be that they included considerable fewer patients than the current study and might have lacked power to demonstrate a significant difference.…”
Section: Discussioncontrasting
confidence: 99%
“…However, these data should be interpreted with caution, because all included studies in the systematic review were cohort studies. Kye et al22 recently published the first study directly comparing stent and acute resection as treatment options for MOPC. Similar to our outcomes, they found laparoscopic resection rate to be significantly higher following stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…The study comparing SEMS and TDT for right‐sided OCRC demonstrated similar technical success and morbidity rates, but clinical success rate was significantly higher in the SEMS group owing to higher decompression efficacy . Kye et al reported that postoperative morbidity, 5‐year OS and DFS were comparable between the SEMS group and the emergency surgery group for right‐sided OCRC. In the present study, although the number was small (n = 15), 3‐year OS and DFS of SEMS‐inserted right‐sided OCRC cases were 100% and 82%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Intestinal obstruction is one of the common presenting symptoms of colorectal cancer. Its incidence is reported as high as 30%, and obstructive colorectal cancer (OCRC) accounted for 85% of colonic emergency . Emergency surgery is usually indicated and this is associated with increased morbidity, mortality, and stoma rate compared to elective surgery.…”
Section: Introductionmentioning
confidence: 99%
“…2 Nevertheless, there are some reasons they would decide on the placement of SEMS for obstructing colon cancer: medically inoperable patients' condition, to avoid multiple staged surgeries (especially for left-sided colon obstruction) and post-operative morbidity, to provide enough preoperative resuscitation and so on. 3 In other words, the preference of SEMS would be intended to achieve favourable perioperative outcomes.…”
Section: Dear Editormentioning
confidence: 99%